## Abstract

As stability and continuous operation are important for almost any use of a microcavity, we demonstrate here experimentally and theoretically a self-stable equilibrium solution for a pump-microcavity system. In this stable equilibrium, intensity- and wavelength-perturbations cause a small thermal resonant-drift that is enough to compensate for the perturbation (noises); consequently the cavity stays warm and loaded as perturbations are self compensated. We also compare here, our theoretical prediction for the thermal line broadening (and for the wavelength hysteretic response) to experimental results.

©2004 Optical Society of America

Full Article |

PDF Article

**More Like This**
### Cited By

Optica participates in Crossref's Cited-By Linking service. Citing articles from Optica Publishing Group journals and other participating publishers are listed here.

Alert me when this article is cited.

### Equations (7)

Equations on this page are rendered with MathJax. Learn more.

(1)
$$N=\frac{2\mathit{\pi r}{c}_{1}\left(1+\epsilon \Delta T\right)}{\frac{{\lambda}_{r}}{\left({n}_{0}+\frac{\mathit{dn}}{\mathit{dT}}\Delta T\right)}}$$
(2)
$${\lambda}_{r}\left(\Delta T\right)\cong {\lambda}_{0}\left[1+\left(\epsilon +\frac{\frac{\mathit{dn}}{\mathit{dT}}}{{n}_{0}}\right)\Delta T\right]\text{}$$
(2)
$$\equiv {\lambda}_{0}\left(1+\phantom{\rule{2.0em}{0ex}}a\phantom{\rule{2.0em}{0ex}}\Delta T\right).$$
(3)
$${\dot{q}}_{\mathit{in}}=I\eta \frac{Q}{{Q}_{\mathit{abs}}}\frac{1}{{\left(\frac{{\lambda}_{p}-{\lambda}_{r}}{\frac{\Delta \lambda}{2}}\right)}^{2}+1}\equiv {I}_{h}\frac{1}{{\left(\frac{{\lambda}_{p}-{\lambda}_{0}\left(1+a\Delta T\right)}{\frac{\Delta \lambda}{2}}\right)}^{2}+1}$$
(4)
$$\mathit{Cp}\phantom{\rule{.2em}{0ex}}\Delta \dot{T}\left(t\right)=\phantom{\rule{4.2em}{0ex}}{\dot{q}}_{\mathit{in}}\phantom{\rule{4.2em}{0ex}}-{\dot{q}}_{\mathit{out}}$$
(4)
$$\phantom{\rule{4.8em}{0ex}}={I}_{h}\frac{1}{{\left(\frac{{\lambda}_{p}-{\lambda}_{0}\left(1+a\Delta T\right)}{\frac{\Delta \lambda}{2}}\right)}^{2}+1}-K\Delta T\left(t\right).$$
(5)
$$0={I}_{h}\frac{1}{{\left(\frac{{\lambda}_{p}-{\lambda}_{0}\left(1+a\Delta T\right)}{\frac{\Delta \lambda}{2}}\right)}^{2}+1}-K\Delta T.$$